Congenital Zika Virus Syndrome: care in light of the Brazilian Unified Health System principles - Gleice Kelli Santana de Andrade; Elen Ferraz Teston; Sonia Silva Marcon; Bianca Cristina Ciccone Giacon-Arruda; Milena Dalariva Amorim; Daniela Miyuki Sato; Josiel Elisandro Werle; Joice Lourenço da Silva (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to know health professionals' perceptions about care actions provided to children with Congenital Zika Virus Syndrome and their families. Methods: this is a qualitative study, carried out in a capital of center-western Brazil, based on the Unified Health System theoretical precepts. Data were collected in September and October 2020, through audio-recorded interviews with 12 health professionals from a specialized service and submitted to analysis of content, thematic modality. Results: the implementation of care actions with these children occurs through multidimensional assessment of children and their families, use of the Unique Therapeutic Project, therapeutic interventions for the development of children and the communication and exchange of interprofessional and family experiences, in addition to considering professionals' prior knowledge and their search for it. Final considerations: children with CZS and their families need individualized, frequent, integrated and continuous care.